Indoor terminal localization technology using a single access point based on distributed MIMO networks - Ze LI; Jian ZOU; Zeng HUANG; Zengshan TIAN (Tongxin xuebao)
Regarding the terminal localization in distributed MIMO networks, an indoor terminal localization system using a single access point (AP) based on distributed MIMO networks was proposed.Firstly, the AP’s antennas were arranged at different locations in the room, and the compressed sensing algorithm was used to estimate the angle of departure (AoD) and time of flight (ToF) of the receiving path on each antenna of the terminal device.Secondly, AoDs and ToFs of multiple paths were combined to establish a nonlinear localization model, and an improved Levenberg-Marquardt algorithm was used to solve the problem.Then, theoretical analysis has been examined for the factors that influence the localization error, and the criteria for the antenna layout was provided.Finally, electromagnetic simulation software was used to build simulation environment and conducted the simulation for system verification.Moreover, software-defined radio platforms were used to conduct practical tests.Both simulation and experimental results indicate that the performance of the proposed localization system is superior to existing single-AP localization systems based on natural multipath.